Internet: Culture, Diversity and Unification - Voiskounsky, Alexander E. (Javnost-The Public, 1999)
The practice of Internet usage is ambiguous as it gives rise to both unification and diversity. This paper analyses cultural specifics of the Internet. The analysis is a preliminary work for an application of socio-historical theory of human mental development. The parameters include techniques of hypertext browsing, the status/position/rank of communicators, the influence of the Internet on communication practices such as holding the floor and turntaking rules, the way emotions are expressed, and the way the English language serves the functions of a world-wide medium.